RESEARCH OF MODERN PROCESSES IN THE RUSSIAN-BELARUSIAN BORDER FOR EDUCATIONAL PURPOSES - Kuzavko, Anton; Silchenkova, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
One of the most important goals of the integration of Russia and Belarus is to pursue a consistent social policy and common economic space. Increased connectivity in border regions (Smolensk, Vitebsk and Mogilev regions) was expected as a result of the integration process. But young people do not see the benefits of creating a Union State. The aim of the research study is to compare the socio-economic indicators of the border regions of Russia and Belarus, to identify current trends in the development of innovations and digitalization in the field of education and in the economy. The following methods were used to achieve the goal: survey, descriptive statistics, time series analysis, comparison, correlation analysis. The main base of the research study is official statistical information. The boundaries of the research study cover the period from 2000 to 2018. As a result of the research study, it was found that GRP growth rates were highest in the Smolensk region. These regions faced problems, including demographic ones. The novelty of the research study lies in identifying the causes of differences in these regions and predicting the prospects for their development.